Search for new phenomena with the MT 2 variable in the all-hadronic final state produced in proton–proton collisions at √s=13TeV - KAYA, MİTHAT (My University, 2017)
© 2017, CERN for the benefit of the CMS collaboration.A search for new phenomena is performed using events with jets and significant transverse momentum imbalance, as inferred through the MT 2 variable. The results are based on a sample of proton–proton collisions collected in 2016 at a center-of-mass energy of 13TeV with the CMS detector and corresponding to an integrated luminosity of 35.9fb-1. No excess event yield is observed above the predicted standard model background, and the results are interpreted as exclusion limits at 95% confidence level on the masses of predicted particles in a variety of simplified models of R-parity conserving supersymmetry. Depending on the details of the model, 95% confidence level lower limits on the gluino (light-flavor squark) masses are placed up to 2025 (1550)GeV. Mass limits as high as 1070 (1175)GeV are set on the masses of top (bottom) squarks. Information is provided to enable re-interpretation of these results, including model-independent limits on the number of non-standard model events for a set of simplified, inclusive search regions.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)